Adverse affects of paclitaxel and carboplatin combination chemotherapy in epithelial gynecologic cancer - Kietpeerakool C. (2014)
Objective: To evaluate the adverse affects of paclitaxel and carboplatin combination chemotherapy. Design: Descriptive cross sectional study Material and Method: Patients with epithelial cancer of the ovary, fallopian tube and peritoneum treated with paclitaxel and carboplatin combination chemotherapy at Chiang Mai University Hospital between August 2003 and August 2004. Results: Of 224 evaluable cycles in 63 patients treated with paclitaxel (175 mg/m 2) and carboplatin (AUC 5), grade 3 and 4 neutropenia occurred in 37.1% or 41.3% of patients. 4.8% of patients experienced febrile neutropenia. Grade 3 and 4 leukopenia occurred in 8.6% of courses and 12.6% of patients. Grade 3 anemia occurred in 5.2% of courses and 9.5% of patients. Grade 3 thrombocytopenia occurred in 2.8% of courses and 9.6% of patients. The nonhematologic adverse affects were rare, however, some adverse events may be potentially life threatening. Conclusion: Adverse affects of paclitaxel and carboplatin combination chemotherapy are acceptable and manageable in the majority of patients.